Progressive Collapse of a Single Layer Schwedler Dome - Hamid, Yazmin Sahol; Kamilan, N. F. (International Journal of Integrated Engineering, 2021)
Large span domes have always drawn architects’ and engineers’ interest as they provide as easy method of roofing large areas with architectural beauty. Single layer Schwedler Dome composed of Circular Hot Hollow Frame (CHHF) is investigated to understand the effects of individual member removal to the behaviour and stability of single layer dome. The major issues of the structural system are related to its instability phenomena whereby it is vulnerable to snap through buckling. The failure of space structure such as Sultan Zainal Abidin Stadium and Bucharest Dome clearly show an understanding of such failure and the behaviour of the space structure is important to develop a safer structure especially in the future. This study deals with a single layer dome having a diameter of 52 m and the span to depth ratio of ½. The loads subjected on the nodes of the structure consists of dead, live and wind loads and assumed to be 1kN each. Due to the symmetric geometry of the dome, the removals were done on the quarter section of the dome only assumed that the loads distribution patterns are similar for each section. This study required 210 members’ removals and the result obtained has been analysed thoroughly. In order to achieve the objectives of the research, computer programming such as FORMIAN, AutoCAD and SAP2000 V18 have been used to generate the geometry of the dome and afterwards analysed the stability of the structure. The numerical technique is based on redistribution of internal loadings due to member’s failure. Critical members are determined by analyzing the Demand Capacity Ratio (DCR) value of each member and identifying the number of overstressed neighboring members. When the internal load of a neighboring member exceeds its loading capacity, the member becomes overstressed and fails which may lead to major collapse of the entire structure. The value of the DCR and the numbers of overstressed members existed in the structure after the removals show the criticality of the section. As a conclusion, this critical area must be considered during analysis, design and construction stage of the dome.